Autologous Blood Transfusion after Local Infiltration Analgesia with Ropivacaine in Total Knee and Hip Arthroplasty. (5th August 2012) - Breindahl, Torben; Simonsen, Ole; Hindersson, Peter; Brødsgaard Dencker, Bjarne; Brouw Jørgensen, Mogens; Rasmussen, Sten
Abstract : Aims . To study the safety of autotransfusion following local infiltration analgesia (LIA) with ropivacaine. Background . Knowledge of blood concentrations of ropivacaine after LIA and autotransfusion is crucial. However, very limited data are available for toxicological risk assessment. Methods . Autotransfusion was studied in patients after total knee arthroplasty (TKA: n = 25 ) and total hip arthroplasty (THA: n = 27 ) with LIA using 200 mg ropivacaine, supplemented with two postoperative bolus injections (150 mg ropivacaine). Drainage blood was reinfused within 6 h postoperatively. Results . Reinfusion caused a significant increase in the serum concentration of total ropivacaine for TKA from 0.54 ± 0.17 (mean ± SD) to 0.79 ± 0.20 μ g/mL (P < 0.001 ) and a nonsignificant increase for THA from 0.62 ± 0.17 to 0.63 ± 0.18 μ g/mL. The maximum free (unbound) concentration after reinfusion was 0.038 μ g/mL. Peak total and free venous ropivacaine concentrations after 8 h and 16 h postoperative bolus injections were 2.6 μ g/mL and 0.11 μ g/mL, respectively. All concentrations observed were below the threshold for toxicity and no side effects were observed. Conclusion . Autotransfusion of patients undergoing knee or hip arthroplasty after local infiltration analgesia with 200 mg ropivacaine can be performed safely, even supplemented with 8 h and 16 h postoperative bolus injections.